Ocean overturning since the Late Cretaceous: Inferences from a new benthic foraminiferal isotope compilation - Cramer, B S; Toggweiler, J R; Wright, J D; Katz, M E; Miller, K G (Paleoceanography and paleoclimatology, 2009)
Benthic foraminiferal oxygen isotopic ( 18 O) and carbon isotopic ( 13 C) trends, constructed from compilations of data series from multiple ocean sites, provide one of the primary means of reconstructing changes in the ocean interior. These records are also widely used as a general climate indicator for comparison with local and more specific marine and terrestrial climate proxy records. We present new benthic foraminiferal 18 O and 13 C compilations for individual ocean basins that provide a robust estimate of benthic foraminiferal stable isotopic variations to ~80 Ma and tentatively to ~110 Ma. First-order variations in interbasinal isotopic gradients delineate transitions from interior ocean heterogeneity during the Late Cretaceous (>~65 Ma) to early Paleogene (3565 Ma) homogeneity and a return to heterogeneity in the late Paleogeneearly Neogene (350 Ma). We propose that these transitions reflect alterations in a first-order characteristic of ocean circulation: the ability of winds to make water in the deep ocean circulate. We document the initiation of large interbasinal 18 O gradients in the early Oligocene and link the variations in interbasinal 18 O gradients from the middle Eocene to Oligocene with the increasing influence of wind-driven mixing due to the gradual tectonic opening of Southern Ocean passages and initiation and strengthening of the Antarctic Circumpolar Current. The role of wind-driven upwelling, possibly associated with a Tethyan Circumequatorial Current, in controlling Late Cretaceous interior ocean heterogeneity should be the subject of further research.